2019
DOI: 10.1111/hae.13899
|View full text |Cite|
|
Sign up to set email alerts
|

Rotational thromboelastometry can predict the probability of bleeding events in a translational rat model of haemophilia A following gene‐based FVIIa prophylaxis

Abstract: Introduction: Monitoring of clinical effectiveness of bypassing agents in haemophilia patients is hampered by the lack of validated laboratory assays. Thromboelastography (TEG) and rotational thromboelastometry (ROTEM) have been evaluated for predicting clinical effectiveness of bypassing agents, however, with limited success. Aim: Application of a longitudinal model-based approach may allow for a quantitative characterization of the link between ROTEM parameters and the probability of bleeding events. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A similar approach (RTTE modeling) has previously been used in HA rats expressing rat FVIIa to correlate a clotting assay parameter with the probability of bleeds. 54 Using this approach, we showed that a reduction in bleeding risk by 80% or 95% compared to untreated rats, required 2.1 and 10 IU/dL of hFVIII (or 0.021 and 0.1 IU/mL), respectively. At a concentration of 10 IU/ dL (0.1 IU/mL or 10% in humans), the probability of experiencing one bleed during the full 12-week study period was 9%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A similar approach (RTTE modeling) has previously been used in HA rats expressing rat FVIIa to correlate a clotting assay parameter with the probability of bleeds. 54 Using this approach, we showed that a reduction in bleeding risk by 80% or 95% compared to untreated rats, required 2.1 and 10 IU/dL of hFVIII (or 0.021 and 0.1 IU/mL), respectively. At a concentration of 10 IU/ dL (0.1 IU/mL or 10% in humans), the probability of experiencing one bleed during the full 12-week study period was 9%.…”
Section: Discussionmentioning
confidence: 95%
“…However, both AAV‐ and protein infusion‐based prophylaxis data were used for an in silico model‐based approach. A similar approach (RTTE modeling) has previously been used in HA rats expressing rat FVIIa to correlate a clotting assay parameter with the probability of bleeds 54 . Using this approach, we showed that a reduction in bleeding risk by 80% or 95% compared to untreated rats, required 2.1 and 10 IU/dL of hFVIII (or 0.021 and 0.1 IU/mL), respectively.…”
Section: Discussionmentioning
confidence: 95%